Anion Transport Across Human Gallbladder Organoids and Monolayers - Zarei, Keyan; Thornell, Ian M.; Stoltz, David A. (Frontiers in Physiology, 2022)
Fluid and anion secretion are important functions of the biliary tract. It has been established that cAMP regulates Na+ absorption through NHE3. However, mechanisms of gallbladder anion transport are less defined. We created organoids and organoid-derived monolayers from human gallbladder tissue to measure organoid swelling and transepithelial electrophysiology. In our in vitro models, forskolin-stimulation caused organoid swelling and increased transepithelial anion transport. Full organoid swelling required Cl−while changes in short-circuit current were HCO3−-dependent. Organoids and monolayers from an individual homozygous for the cystic fibrosis-causing ΔF508 CFTR mutation had no apical expression of CFTR and minimal changes in transepithelial current and conductance with forskolin treatment. However, organoid swelling remained intact. Dilution potential studies revealed that forskolin treatment increased the paracellular permeability to anions relative to cations. These data suggest a novel paracellular contribution to forskolin-stimulated fluid transport across the gallbladder epithelium.